BINUS University: Bioinformatics Road Map - Prabowo, Harjanto; Abbas, Bahtiar S.; Pardamean, Bens (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45479097/BINUS-University-Bioinformatics-Road-Map